The impact of fast ferry traffic on underwater optics and sediment resuspension - Ants Erm; Tarmo Soomere (Oceanologia, 2006)
Wake waves produced by fast ferries bring about significant changesin the optical parameters of sea water in the c. 1 m thick near-bottomlayer of the coastal areas of Tallinn Bay. The greatest of thesechanges occur at relatively small depths, but the duration ofthe influence increases with increasing depth. Rough quantitativeestimates suggest that the overall influence of fast ferry trafficin Tallinn Bay may result in an annual loss of the order of severalhundred litres of fine sediments from each metre of the coastline.